The relationship between mindfulness and subjective well-being among Filipino seminarians - Asiatico, Ma. Dinah Espartero (Animo Repository, 2014)
The aim of this study was to determine the relationship between mindfulness and subjective well-being among seminarians who went on a five-week mindfulness program. A mixed method research design was used in this study. Correlation was used to see possible relationships among five aspects of mindfulness, global mindfulness, amount of practice time and subjective well-being. Paired samples t-test was used to compare scores before and after the mindfulness program on five aspects of mindfulness and subjective well-being. It also sought to know if there are perceived impacts of mindfulness on subjective well-being. Results indicated that all five aspects of mindfulness increased after the mindfulness program as seen in the increased mean scores. There was a link between global mindfulness and subjective wellbeing with a significant change in correlation after the mindfulness program was done. Observing aspect also showed a significant relationship with subjective well-being. Mindfulness was seen as related to seminarians subjective well-being after the mindfulness program. Furthermore, there was an improvement in their mindfulness aspects, and seminarians view that there is a significant relationship between ones mindfulness and their subjective well-being as further explored in the interviews. Generally, the seminarians improved their understanding of themselves through self-appreciation and self-recognition. Their interpersonal relationship improved through compassion and taking responsible actions. A better coping style emerged through discovery of other possible conflict resolution strategies. Overall, the seminarians subjective well-being improved in the areas of the self, relationship to others and physical wellbeing.